Artificial Ascites in Radiofrequency Ablation for Liver Cancer - Rino Alvani Gani (The Indonesian Society for Digestive Endoscopy, 2017)
Background: Radio Frequency Ablation (RFA) is one of the treatment modality for liver tumor either as primary tumor as well as secondary malignancy. Occasionally, a good ablation can’t be performed due to the tumor location. To assists the ablation in this particular case, some fluid can be deposited inside the abdomen which is called as artificial ascites. The aim of this study is to report and evaluate the method of artificial ascites in RFAMethod: This was a case series study consist of 19 consecutive patients that had been treated with ultrasound-guided RFA using artificial ascites from 2014 to 2017.Result: Artificial ascites was successfully performed in all 19 patients (100%) with total of 53 hepatocellular carcinoma (HCC) lesions in 34 RFA’s sessions and tumor size ranges from 10mm to 50mm. Most of the tumors were primary tumor (14/19). 9 patients had single tumor and 10 patients had multiple tumors and most of the tumor were located in segment 5 (14/53). Artificial ascites was performed using 5% dextrose in water (D/W)solution ranging from 500ml to 1500ml. No adverse effect occurred during and after the procedure.Conclusion: Percutaneous RFA using artificial ascites technique was safe and effective fortreating HCC